PEMBERDAYAAN MASYARAKAT DESA WANUREJO DALAM MENGATASI STUNTING, ATS, DAN POTENSI DESA MELALUI KEGIATAN KKN - Fadhia Bimala Nur Insani; Emma Dwi Ratnasari; Haura Amorita; Annisa Sofia Fitriyanti; Cita Pranawengrum; Sabrina Nur Fauziah; Tegar Nur Sila; Fatkurohman; Althaf Rafif Jauharsyah; Riduwan Maulana; Finosa Farhan Teja (PPM Sdirjianbang Akademi Militer, 2025)
Wanurejo Village, located in Borobudur District, Magelang Regency, faces several critical challenges affecting the welfare of its community, including high rates of out-of-school children (ATS), stunting, and the utilization of tourism potential as well as leftover rice. This community service program aims to address these issues through several strategic interventions with a qualitative approach. The methods used include observation, in-depth interviews, and document studies. The results of the program show that technical issues in the ATS data verification system and internet connectivity have hampered the data collection process, but solutions such as training and infrastructure improvements have helped to improve the situation. Stunting mitigation was successful through the provision of supplementary food, socialization of the mother and child health (KIA) book, and regular posyandu (integrated health service) activities, which increased community awareness and understanding. Initiatives for tourism branding and training on utilizing leftover rice for crackers have also enhanced the village's economic potential and community awareness. These findings demonstrate a significant improvement in community welfare and provide a model of village empowerment that can be adapted by other villages facing similar challenges.